Are your clients having fun?" the implications of respondents' preferences for the delivery of group exercise programs for falls prevention - McPhate, L.; Simek, E.; Haines, T.; Hill, Keith; Finch, C.; Day, L. (Human Kinetics Inc, 2016)
Background: Group exercise has been shown to be effective in preventing falls; however, adherence to these interventions is often poor. Older adults' preferences for how these programs can be delivered are unknown. Objective: To identify older people's preferences for how group exercise programs for falls prevention can be delivered. Design: A two-wave, cross-sectional, state-wide telephone survey was undertaken. Respondents were community-dwelling men and women aged 70+ in Victoria, Australia. Methods: Open-ended questions were asked to elicit information regarding respondent preferences of the program, which were analyzed using a framework approach. Results: Ninety-seven respondents completed the follow-up survey. The results indicate that older adults most frequently report the short-term advantages and disadvantages when describing their preferences for group exercise, such as enjoyment, social interaction, and leader qualities. Longer-term advantages such as falls prevention were described less frequently. Conclusions: This study indicates the importance of interpersonal skills, and that the opportunity for social interaction should not be overlooked as a positive feature of a group exercise program.